Epigeneti-What? Approaches on Translating Research for Primary Breast Cancer Prevention - Perrault, Evan K.; Hildenbrand, Grace M.; Nyaga, Robert G. (Frontiers in Oncology, 2019)
In fiscal year 2017, the National Cancer Institute devoted more than a half-billion dollars to breast cancer research. Since 2012, the total investment has been more than $3 billion. Despite this significant investment, breast cancer still has no known immediate causes as it generally develops over the life course. Therefore, research is unable to provide the public any sort of magic bullet, or conclusive link between certain environmental exposures and the development of breast cancer later in life. What research is only able to report are likelihoods – possible links – things people might want to consider avoiding or doing in their everyday lives to reduce their future risks of developing breast cancer. This abundance of rigorously performed, albeit causally inconclusive, research focused on “plausible” links poses a challenge for health communicators who are tasked with seeking to find ways to translate this science into advice that people can act upon today. However, if society must wait for the science to provide 100% conclusive evidence before anyone ever takes action, how many lives could have been saved in the interim? Therefore, we advocate a two-pronged approach to translating scientific findings regarding environmental exposures and breast cancer prevention: a bottom-up approach – focused on informing the lay public and individuals, while simultaneously performing a top-down approach – focused on influencing policymakers. The current perspective analyzes the strengths and weaknesses to both approaches, and encourages scientists to work closely with health communicators to develop theoretically-driven strategies to drive positive changes over time.